Appropriate timing of treatment contributes to better root development of impacted anterior teeth in children - Wang, Yi; Chen, Xiaoqian; Zhou, Dan; Zheng, Liwei; Li, Xiaobing; Peng, Yiran (American journal of orthodontics and dentofacial orthopedics, 2024)
This study investigated the effects of different timings of orthodontic treatment on the root development of impacted anterior teeth in children. The cone-beam computed tomography (CBCT) data of 45 children with impacted anterior teeth were divided into unformed root (UR) group or basically formed root (BFR) group to evaluate root length (RL) and root growth length (RGL) of impacted teeth and contralateral nonimpacted teeth pretreatment and posttreatment. In addition, 22 patients with impacted dilaceration were selected to assess the effects of the crown-root angle and root development stage on RL and RGL. The Student t test, Wilcoxon test, analysis of variance, and multiple linear regression analysis were used for statistical evaluations. The RL of treated impacted teeth pretreatment and posttreatment was significantly shorter than contralateral nonimpacted teeth values (P <0.05). Posttreatment, the RL and RGL of impacted teeth of the UR group were significantly greater than those of the BFR group (P <0.05). The RGL of the dilacerated root in the UR group was considerably higher than in the BFR group (P <0.05). The larger crown-root angle group had a longer posttreatment RL (P <0.05). Multiple linear regression analysis revealed that the Nolla stage of impacted teeth and RL of contralateral teeth pretreatment significantly influenced the RL of impacted teeth posttreatment. Prompt orthodontic treatment is necessary for children with impacted anterior teeth to release the impacted state and achieve better root development. The root length of a dilacerated tooth continued to develop under treatment, but the crown-root angle partly constrained it. •Impacted teeth treated with earlier Nolla stage can get better root prognosis.•The crown-root angle partly constrained the root length growth of dilacerated tooth.•Early treatment releases the impacted state and augments the root development potential.